1970
DOI: 10.1136/jech.24.1.63-a
|View full text |Cite
|
Sign up to set email alerts
|

Second primary cancers in patients with tumours of the salivary glands.

Abstract: Rates for juveniles before the courts have nearly doubled in a decade in England and Wales. Data from an epidemiological study of all the children in one community who make court appearances have been collected over nine years. Enumeration district delinquency rates for first court appearances by boys show wide and consistent differences over seven years. Similarly, such first appearance rates for schools show wide and consistent differences. No comparable data on the distribution of family disruption in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 0 publications
1
20
1
Order By: Relevance
“…Despite this, we were unable to confirm a significant increase in risk of breast cancer, as has been reported by Berg et al (1968) and by Prior & Waterhouse (1977), but not found by Moertel & Elveback (1969) or Dunn et al (1972). (Table II) The small excess we observed was not statistically significant, but the relative risk of 1.3 fell within the confidence intervals of all earlier studies except that by Berg et al (1968).…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Despite this, we were unable to confirm a significant increase in risk of breast cancer, as has been reported by Berg et al (1968) and by Prior & Waterhouse (1977), but not found by Moertel & Elveback (1969) or Dunn et al (1972). (Table II) The small excess we observed was not statistically significant, but the relative risk of 1.3 fell within the confidence intervals of all earlier studies except that by Berg et al (1968).…”
Section: Discussioncontrasting
confidence: 89%
“…Bronchial cancer excesses were also observed in the study by Prior & Waterhouse (1977). They raise the possibility that the excesses might be due to an underestimate of the expected number of bronchial cancers, since the rates of lung cancer changed dramatically over the period of their study but were averaged to provide an expected number.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…An association between salivary gland carcinoma and second primary breast cancer has been previously noted in several studies. [16][17][18] In 1 study, a 2.5-fold risk for breast cancer was shown after both benign and malignant salivary gland tumors. 19 On the contrary, Biggar et al 20 did not find an increased breast cancer risk after salivary gland carcinoma.…”
Section: Introductionmentioning
confidence: 99%